2015
DOI: 10.1513/annalsats.201502-105oc
|View full text |Cite
|
Sign up to set email alerts
|

Small Pulmonary Artery Defects Are Not Reliable Indicators of Pulmonary Embolism

Abstract: There is relatively poor interobserver agreement for subsegmental and/or small pulmonary artery defects, especially in CT pulmonary angiograms degraded by technical artifacts. These factors can lead to an increased frequency of inaccurate interpretation or indeterminate diagnosis of subsegmental and/or small defects. Caution is indicated in interpreting the significance of small vascular defects in CT pulmonary angiograms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
33
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 14 publications
0
33
1
3
Order By: Relevance
“…Ghanima et al (2007) found a low inter‐observer agreement of 25%, with a kappa of 0·38 (95% CI 0·0–0·89). Although our data do not allow firm conclusions on the reasons for the difference between the current and prior studies, we hypothesize that the further advancements in CT technology since 2002–2008 [inclusion period of the studies reported by Ghanima et al (2007) and Miller et al (2015)] and the very low number of technically inadequate CT scans in the YEARS study may have contributed to the good inter‐observer agreement found in the current analysis.…”
Section: Discussioncontrasting
confidence: 66%
“…Ghanima et al (2007) found a low inter‐observer agreement of 25%, with a kappa of 0·38 (95% CI 0·0–0·89). Although our data do not allow firm conclusions on the reasons for the difference between the current and prior studies, we hypothesize that the further advancements in CT technology since 2002–2008 [inclusion period of the studies reported by Ghanima et al (2007) and Miller et al (2015)] and the very low number of technically inadequate CT scans in the YEARS study may have contributed to the good inter‐observer agreement found in the current analysis.…”
Section: Discussioncontrasting
confidence: 66%
“…Two recent studies specifically reviewed positive scans using specialist cardiothoracic radiologist reviews found rates of SSPE of 18% (yield 19%- Hutchinson, Eire) and 26% (yield 9%, Miller, USA). [6,38] Both studies found very high rates of probable or definitive false positive diagnoses (56% and 42% respectively) amongst CTPA reported as isolated SSPE or isolated segmental PE. It seems likely that there are differences between sites and regions in radiology reporting practice, with institutional or regional willingness to “miss” PE potentially explaining some of this variation.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that if utilisation rates doubled and yield routinely dropped to well below 10%, as seems to be the case in significant parts of the USA, that small: large PE ratios may change. [3,38,39]…”
Section: Discussionmentioning
confidence: 99%
“…51 Considering that there are hundreds of subsegmental arteries, it is unlikely that their radiological assessment is as complete as in the case of the 18 segmental, 5 lobar, and 2 main pulmonary arteries. 49 Quality of imaging is also an important variable affecting scan interpretation. In most cases, the CTPA scans are inconclusive or false positive due to suboptimal vessel opacification, as well as respiratory and heart pulsation artifacts.…”
mentioning
confidence: 99%
“…Obesity and a mucus plug adjacent to the pulmonary artery may also considerably affect the quality of the CTPA images, leading to artifactual findings and overdiagnosis. 48,49,52 It seems unclear if the clinical presentation of symptomatic SSPE is similar to that of more proximal PE. A systematic review, which compared patients with SSPE and those with more proximal PE, reported that patients with SSPE were less likely to complain of dyspnea (66.7% vs 84%, respectively), and most cases in that study untreated patients do not have worse prognosis.…”
mentioning
confidence: 99%